UJI TOTAL FLAVONOID DAN UJI AKTIVITAS EKSTRAK METANOL DAUN JERUJU (Acanthus ilicifolius.L) TERHADAP BAKTERI STREPTOCOCCUS MUTANS - Dewi Fitriani Puspitasari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
AbstractThis study aims to determine the antibacterial activity, effective concentration and the effect of increasing the concentration of methanol extract of Jeruju leaves (Acanthus ilicifolius) on the growth inhibition of Streptococcus Mutans bacteria. Extraction was carried out by maceration using methanol as a solvent. Testing of antibacterial activity using agar diffusion method (modified Kirby and Bauer diffusion) by means of wells. The results of the antibacterial activity were analyzed using the One way ANOVA method. Anova data showed that extract concentrations of 8%, 10%, 20%, 30% had given activity inhibiting the growth of the test bacteria, namely 15.74 mm; 20.50 mm; 21.11mm and 21.66mm. The increase in the concentration of jeruju leaf extract showed the larger the diameter of the inhibition zone for bacterial growth. The increase in the diameter of the inhibition zone showed a significant difference in p0.05 at each concentration.